Wage Discrimination Based on the Country of Birth: Do Tenure and Product Market Competition Matter? - Valentine Fays; Benoît Mahy; François Rycx; Mélanie Volral (Institute of Labor Economics (IZA), 2019)
Using a merged employer-employee panel dataset of 13,000 firms for the 1999-2010 period, this paper aims to quantify wage discrimination against migrant workers based on their countries of birth, with workers' tenure and firm product market competition as moderator variables. To do so, we specify a wage-setting equation \~A la Bartolucci (2014) that includes a direct measure of worker productivity. We control for a wide range of worker and firm characteristics, as well as time-invariant unobserved heterogeneity in firms and potential endogeneity in the composition of the workforce. Our preferred results estimate that wage discrimination against non-EU15 workers in Belgium is in the order of 6.1%. This figure hides large disparities in wage discrimination against foreign-born migrants depending on their countries of birth, as well as the vanishing of wage discrimination against migrants with tenure. Our results also suggest that wage discrimination disappears in highly competitive product market situations.
Keywords: J24; J71; D41; 330; product market competition; tenure; workers' countries of birth; wage discrimination; migrants; direct productivity measure